Which factors influence women in the decision to breastfeed? - Canicali Primo, Cândida; de Oliveira Nunes, Bruna; de Fátima Almeida Lima, Eliane; Costa Leite, Franciele Marabotti; Barros de Pontes, Monica; Gomes Brandão, Marcos Antônio (Investigación y Educación en Enfermería, 2016)
Objective. Identify the factors that influence women in the decision to breastfeed. Methods. Integrative review. Information was gathered from original articles, case studies, theoretical studies, consensus and systematic reviews published between 2007-2013 in Spanish, Portuguese and English and recovered in the databases MEDLINE and LILACS. The descriptors used in this study were: breastfeeding, maternal behavior, risk factors, lactation and newborn. Results. Were included 30 articles, grouped into five categories. Factors influencing the decision of the breastfeeding woman are a convergence of breastfeeding´s advantages, benefits and justifications, family, social and professional support, sociodemographic and clinical characteristics of women, personal experience and family tradition and personal choice. Conclusion. The decision to breastfeed by women is influenced by a convergence of factors. It is essential the role of nursing to encourage women in the decision to initiate and maintain breastfeeding her child. How to cite this article: Primo CC, Nunes BP, Lima EFA, Leite FMC, Pontes MB, Brandão MAG. Which factors influence women in the decision to breastfeed? Invest Educ Enferm. 2016; 34(1): 198-210